Detection of Mycobacterium bovis and Klebsiella pneumoniae at Bali Cattle Slaughterhouse by culture analysis and PCR - Oka Darsana, I Gede; Dibia, I Nyoman; Mahatmi, Hapsari (Veterinary Science and Medicine Journal; Vol 3 No 2 (2015), 2015)
A study to determine the presence and prevalence of bovine tuberculosis and Klebsiella pneumoniae atcattle slaughterhouse in Bali was carried out in Pesanggaran and Mambal abattoirs from January to March2015.The Lungs and lymph nodes were inspected for lesions and then examined through DNA analysis forMycobacterium bovis and culture for isolation of Klebsiella pneumoniae. Of the samples examined, no onehad lesions suggestive of tuberculosis in two abattoirs.However, Klebsiella pneumoniae was observed1/4513 sample (0.02%) only in Mambal abattoir. This study is the first report of the presence of Klebsiellapneumoniae in Bali. Therefore, a aware of this zoonotic Klebsiellosis and its control managementformulation are need.
Keywords: Bali Cattle; Mycobacterium bovis; Klebsiella pneumoniae; prevalence